Ammonium transporter PsAMT1.2 from Populus simonii functions in nitrogen uptake and salt resistance. (17th May 2021) - Li, Wenxin; Feng, Zimao; Zhang, Chunxia
Abstract: Ammonium (NH4 + ) is a primary nitrogen (N) source for many species, and NH4 + uptake is mediated by various transporters. However, the effects of NH4 + transporters on N uptake and metabolism under salt stress remain unclear. In the present study, we investigated the expression characteristics and transport function of PsAMT1.2 in Populus simonii and its role in ammonium uptake and metabolism under salt stress. PsAMT1.2 was localized in the plasma membrane highly expressed in the roots. Heterologous functionality tests demonstrated that PsAMT1.2 mediates NH4 + permeation across the plasma membrane in yeast mutants, restoring growth. A short-term NH4 + uptake experiment showed that PsAMT1.2 is a high-affinity NH4 + transporter with a Km value of 80.603 μM for NH4 + . Compared with the wild type (WT, Populus tremula × Populus alba INRA 717-IB4 genotype), PsAMT1.2- overexpressing transgenic poplar grew better, with higher increases in stem height and relative chlorophyll content under both control and salt-stress conditions. PsAMT1.2 overexpression significantly increased the total NH4 + concentration and total N of whole plants under salt stress. The glutamate synthase (GS), glutamine synthetase (GOGAT) and glutamate dehydrogenase (GDH) activities and the total amino acids largely increased in the roots of PsAMT1.2- overexpressing transgenic plants compared with the WT plants under control conditions, suggesting that PsAMT1.2 overexpression promotes NH4 + assimilation and metabolism in poplar roots. Consistent with the increased total amino acid content, GS1.3, GS2 and Fd-GOGAT expression was upregulated in the roots and leaves of the PsAMT1.2- overexpressing transgenic plants compared with the WT plants under salt stress. Collectively, PsAMT1.2 encodes a high-affinity NH4 + transporter crucial to NH4 + uptake and metabolism under salt stress.